New Paths in Working Time Policy - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2001)
New Paths in Working Time Policy, edited by jean-Yves Boulin and Reiner Hoffmann, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Human resource management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Working hours